2019
DOI: 10.1016/j.chom.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Mucispirillum schaedleri Antagonizes Salmonella Virulence to Protect Mice against Colitis

Abstract: Highlights d Mucispirillum schaedleri confers protection against Salmonella colitis in mice d Salmonella and M. schaedleri compete for anaerobic respiration substrates in the gut d M. schaedleri restricts Salmonella infection and inhibits virulence factor expression d Mucispirillum spp. are enriched in human gut mucosal samples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
179
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 241 publications
(190 citation statements)
references
References 84 publications
(99 reference statements)
10
179
1
Order By: Relevance
“…M schaedleri had been reported to be a mucus inhabitant and was widely associated with intestinal inflammation . A recent study revealed a high prevalence of M schaedleri in human mucosal biopsy samples, further suggestive of the potential important role of M schaedleri in human diseases. Here, we demonstrated the presence of M schaedleri in livers of mice with isolated steatosis and NASH.…”
Section: Discussionmentioning
confidence: 96%
“…M schaedleri had been reported to be a mucus inhabitant and was widely associated with intestinal inflammation . A recent study revealed a high prevalence of M schaedleri in human mucosal biopsy samples, further suggestive of the potential important role of M schaedleri in human diseases. Here, we demonstrated the presence of M schaedleri in livers of mice with isolated steatosis and NASH.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, in male mice, DHA selectively increased butyrate‐producing Coprococcus [ 47 ] while suppressed pro‐inflammatory species Streptococcus [ 48 ] and p‐75‐a5 which were strongly correlated with HOMA‐IR and LPS production in our study. EPA selectively enriched the abundances of Mucispirillum schaedleri [ 49 ] and Barnesiella [ 50 ] which have been suggested to counteract colitis in mice and elevated S24‐7 [ 51 ] and Barnesiella [ 52 ] linked with ameliorated glucose metabolism, whereas substantially abolished SCFA‐producing Clostridium XlVa [ 53 ] which might explain the unchanged levels of propionate and butyrate in male mice. In female mice, DHA specifically decreased the abundance of pro‐inflammatory Enterorhabdus [ 54 ] and promoted the growth of butyrate‐producing Intestinimonas [ 55 ] and Bacteroides acidifaciens [ 56 ] which were shown to prevent obesity and improve insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that the gnotobiotic OMM 12 model is particularly well suited to study the molecular mechanisms involved in phage bacteria dynamics in the gut. OMM 12 community establishes a longterm stable composition over several mouse generations and can be used as platform to flexibly incorporate additional bacterial strains to the community , Herp et al 2019, Studer et al 2016. Interestingly, Hsu and colleagues recently reported the use of similar synthetic microbiota models to study phage bacteria interactions with two major differences.…”
Section: Discussionmentioning
confidence: 99%